2021
DOI: 10.1108/ijse-11-2018-0623
|View full text |Cite
|
Sign up to set email alerts
|

Financial sector development and life insurance inclusion in India: an ARDL bounds testing approach

Abstract: PurposeThis paper analyses the relationship between financial sector development (FSD) and life insurance inclusion in India during the period from 1971–1972 to 2016–2017. The study analyses the effect of financial deepening on life insurance inclusion in India.Design/methodology/approachThe study employs augmented Dickey–Fuller (ADF) unit roots test to check the stationarity properties of the time series data. It estimates a life insurance inclusion model using the auto-regressive distributed lag model (ARDL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(40 reference statements)
1
1
0
Order By: Relevance
“…Findings of the study according to table 3 indicate that income level has a negative statistically significant influence on life insurance development (-0.30, P-value<0.05) hence the null hypothesis is rejected. The study's findings are consistent with the findings of Mathew and Sivaraman (2021), who confirm that income is negatively related to life insurance consumption, and Bhatia and Jain (2013), who confirm that income level measured by per capita GDP negatively affects the growth of insurance penetration. In line with this study, Alhassan and Biekpe (2016) and Kabrt (2021) and Segodi & Athenia (2022) confirmed that income led to a decline in life insurance development.…”
Section: Regression Analysis and Discussion Of Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…Findings of the study according to table 3 indicate that income level has a negative statistically significant influence on life insurance development (-0.30, P-value<0.05) hence the null hypothesis is rejected. The study's findings are consistent with the findings of Mathew and Sivaraman (2021), who confirm that income is negatively related to life insurance consumption, and Bhatia and Jain (2013), who confirm that income level measured by per capita GDP negatively affects the growth of insurance penetration. In line with this study, Alhassan and Biekpe (2016) and Kabrt (2021) and Segodi & Athenia (2022) confirmed that income led to a decline in life insurance development.…”
Section: Regression Analysis and Discussion Of Findingssupporting
confidence: 89%
“…Milijana et al (2017) confirm that GDP has a positive influence while interest rates have a negative influence on life insurance development. Furthermore, Mathew and Sivaraman (2021) confirmed that interest and income are negatively related to life insurance development. In light of these contradictory findings from previous empirical studies, the following null hypotheses were developed and tested by the study: H1: There is no statistically significant relationship between interest rates and life insurance sector development in Tanzania H2: There is no statistically significant relationship between income level and life insurance sector development in Tanzania H3: There is no statistically significant relationship between domestic saving and life insurance sector development in Tanzania H4: There is no statistically significant relationship between financial depth and life insurance sector development in Tanzania H5: There is no statistically significant relationship between inflation rate and life insurance sector development in Tanzania…”
Section: Relevant Literature Review and Hypothesis Developmentmentioning
confidence: 65%